Development of the gaming simulation for urban renewal project : case study on the renewal project of residential area in Seoul, Korea - Kang, Yang Suk; Kaji, Hideki; Angel, Shlomo; Archer, Raymon W.; Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1981)
Th e process of city growth to arrive at a perfectly balanced development in all aspects is difficult to attain. Like any other organisms, there can be parts which can become obsolescent. Very often, a city is depicted as a representive of an era to show man's progress in his quest to improve the quality of life based on his goals and aspirations. Thus, more people went to the cities in search f or a better standard. of living because in big cities industries are developed. However, this has resulted to overcrowding which affects severely the quality of human life. Among the felt needs in big cities is housing--as a shelter and where family interactions/activities are carried on. Ironically, big cities are popular for so many reasons but it is here that deplorable housing conditions exist. As a solution of such problem, one of the approaches adopted is the renewal of residential areas. The target group s of this renewal residential area programme are the low-income dwellers. However , the houses constructed under this programme are beyond the means of most of the target clients. Consequently , the middle and some high income dwellers moved in and many low-income dwellers moved out for they could not afford to pay the newly constructed houses. Thus, in effect , the renewal residential area projects have created more homeless families among the low-income groups. For the last decades, gaming simulation as one of the techniques of urban planning has gained recognition and acceptance. However,. this technique bas never been developed and applied in residential renewal programmes. But based on this, it was found out that gaming simulation can be a good tool for this programme. This study consists of two main parts: 1. General Study of housing situations a n d problems in Korea; and 2. Development oi gaming simulation in residential renewal are as.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Urban renewal -- Korea -- Seoul -- Simulation methods